Processing contaminants in edible oils : MCPD and glycidyl esters - MacMahon, Shaun, 1976-; Beekman, Jessica K. (Academic Press, 2022)
Fully revised and updated, Processing Contaminants in Edible Oils, 2nd edition, presents the latest research on monochloropropanediol (MCPD) and glycidyl esters in edible oils. These potentially harmful contaminants are formed during the industrial processing of food oils during deodorization. A number of advancements in understanding these have been made since the publication of the first edition. These important changes, which impact industrial mitigation, analytical methods, toxicology and regulation, are highlighted for up-to-date reference. The mechanisms of formation for MCPD and glycidyl ester contaminants, as well as research identifying possible precursor molecules are reviewed, as are strategies which have been used successfully to decrease the concentrations of these contaminants. From the removal of precursor molecules before processing, modifications of deodorization protocol, to approaches for the removal of these contaminants after the completion of processing, methods of mitigating and eliminating contaminants are presented.